The major histocompatibility complex region and diversity of the local chicken populations in Niger - Hassan Ousseini, M.; Machuka, Eunice M.; Kyallo, Martina M.; Tiambo, Christian K.; Domelevo Entfellner, Jean-Baka; Pelle, Roger (Rovedar, 2023)
Introduction: The major histocompatibility complex (MHC) of chicken is highly polymorphic, and it is linked to several disease resistance or susceptibility traits. Therefore, the current study aimed to analyze the genetic diversity in the MHC region of Nigerien local chicken (Dourgou, Goggori, Kolonto, Tchagara, Gouzou-gouzou, and Popular) using a high polymorphic microsatellite marker named LEI0258 to determine the diversity of chickens kept at the four agroecological zones in Niger.